Book review: Embodied Approaches to Supervision: The Listening Body By Celine Butté and Tasha Colbert - M. McFarlane (Scottish Journal of Residential Child Care)
Embodied Approaches to Supervision contains ten chapters written by dance movement psychotherapists, who each present their views of the ways in which embodiment practices can be used in supervision. Embodied practice utilises the mind-body connection and is described in the introductory page of the book as 'the intimate and dynamic interaction between mind and body'. Embodiment approaches may be particularly applicable to young people in residential care, who may have experienced bodily traumas such as physical and sexual abuse and may not always have the language to communicate their experiences verbally.